ANALYSIS OF THE PRICE UNIT PRICE CONTRACT IN THE REHABILITATION CONSTRUCTION PROJECT BUILDING FACILITIES OF PUBLIC WORKS AND THE ADMINISTRATION OF THE SAMARINDA CITY SPACE - LUKAS, FERDINAN (KURVA S JURNAL MAHASISWA, 2020)
The contract is an agreement between the service user (owner) and the service provider (contractor) to make a transaction in the form of a capability between the service provider to do something for the service user with a sum of money in exchange for the results of negotiations and negotiations between the two parties. The contract is an agreement between the service user (owner) and the service provider (contractor) to make a transaction in the form of a capability between the service provider to do something for the service user with a sum of money in exchange for the results of negotiations and negotiations between the two parties. n this study the validity test and reliability test are used to determine an item to be used. The application of work contracts in the construction projects for public works infrastructure and public space construction in Samarinda is still poorly implemented in the field. And as for the indicators that affect the employment contract there are still many obstacles that affect the contract